1978
DOI: 10.1159/000207703
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Pattern in <i>β</i>-Thalassaemia

Abstract: Serum lipids, phospholipid fractions and the composition of serum lipid fatty acids were studied in 20 children presenting β-thalassaemia major, 20 heterozygous children and 20 normal controls. Total serum phospholipids, their fractions and cholesterol were significantly lower in patients with thalassaemia major. These changes were referred to hepatic damage and to severe anaemia, respectively. Some serum lipid polyunsaturated fatty acids were significantly decreased in patients with thalassaemia major as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…In the same study it was shown that the levels of serum lipid multiple unsaturated fatty acids decreased [21]. Those changes appear as a result of excessive iron-loading and liver damage [21]. Serum total cholesterol level has been found to be low, in accordance with the study we performed in patients with B-TM.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the same study it was shown that the levels of serum lipid multiple unsaturated fatty acids decreased [21]. Those changes appear as a result of excessive iron-loading and liver damage [21]. Serum total cholesterol level has been found to be low, in accordance with the study we performed in patients with B-TM.…”
Section: Discussionsupporting
confidence: 76%
“…A study demonstrated that total phospholipids and its functions also decrease with the decrease of total cholesterol [21]. In the same study it was shown that the levels of serum lipid multiple unsaturated fatty acids decreased [21]. Those changes appear as a result of excessive iron-loading and liver damage [21].…”
Section: Discussionmentioning
confidence: 96%
“…LDL/HDL ratios increase from controls < non-transfused < transfused < long-term transfused patients. Abnormal serum lipid and lipoprotein patterns had been reported in thalassemia patients [8,17]. However, in this context, not only lipid metabolism must be considered, but also the effect of generally decreased cholesterol levels on biosynthesis of steroids in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 In our study, we found MDA levels (nmol/mL) to be significantly increased in b thalassemia patients as compared to controls. Giardini et al 21 demonstrated that red blood cell MDA was significantly higher in b thalassemia patients as compared to controls. Livrea 8 showed that the mean concentrations of lipoperoxides evaluated as malondialdehyde/thiobarbituric acid (MDA/TBA) adducts, increased about twofold in their thalassemic patients with respect to controls.…”
Section: Articlementioning
confidence: 99%